2018
DOI: 10.7717/peerj.5231
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tracking of juvenile whale sharks in the Sulu and Bohol Seas, Philippines

Abstract: The whale shark Rhincodon typus was uplisted to ‘Endangered’ in the 2016 IUCN Red List due to >50% population decline, largely caused by continued exploitation in the Indo-Pacific. Though the Philippines protected the whale shark in 1998, concerns remain due to continued take in regional waters. In light of this, understanding the movements of whale sharks in the Philippines, one of the most important hotspots for the species, is vital. We tagged 17 juvenile whale sharks with towed SPOT5 tags from three genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Since most whale shark aggregations occur in coastal waters (Rowat and Brooks, 2012) this use of more offshore waters by adults would explain why immature sharks dominate the aggregations. This use of shallower continental shelf habitat for juvenile whale sharks is not exclusive as several studies, including the current study, have reported juveniles to use offshore waters as well (Hsu et al, 2007;Araujo et al, 2018;Diamant et al, 2018). Additional tracking and dietary studies on juvenile and adult whale sharks will be instrumental in better describing stagespecific movement patterns.…”
Section: Size Distributionmentioning
confidence: 69%
See 2 more Smart Citations
“…Since most whale shark aggregations occur in coastal waters (Rowat and Brooks, 2012) this use of more offshore waters by adults would explain why immature sharks dominate the aggregations. This use of shallower continental shelf habitat for juvenile whale sharks is not exclusive as several studies, including the current study, have reported juveniles to use offshore waters as well (Hsu et al, 2007;Araujo et al, 2018;Diamant et al, 2018). Additional tracking and dietary studies on juvenile and adult whale sharks will be instrumental in better describing stagespecific movement patterns.…”
Section: Size Distributionmentioning
confidence: 69%
“…These seasonal offshore movements away from known foraging areas is supported by the other whale shark tagging study in the region by Hueter et al (2013), who reported whale shark movements from the southern GOM, with similar timings of movements away from the summer aggregation site during fall. Further supporting this is that as prey abundance at localized seasonal aggregation sites wanes, whale sharks leave these areas to undergo broad scale movements in search of other foraging opportunities (de la Parra Venegas et al, 2011;Hueter et al, 2013;Araujo et al, 2018). The ultimate purpose of the movements away from the northern GOM during fall and winter is unknown, however, as observed in other regions these movements could represent searching for additional foraging opportunities and possibly movements to more productive overwintering grounds in the GOM.…”
Section: Discussion Seasonal Occurrence Distribution and Movementsmentioning
confidence: 91%
See 1 more Smart Citation
“…The whale sharks at Oslob that feed at the surface for extended periods of time (often 6 am to 1 pm) are exposed to higher temperatures and more direct sun exposure than would be typical (e.g. 30,[42][43][44][45] ). The prolonged sun exposure on shallow waters with a sandy substrate reflects sunlight which might cause skin darkening on the www.nature.com/scientificreports/ ventral side of the animals (GA, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Whale sharks form predictable aggregations across the globe, normally linked to primary productivity or feeding opportunities ( e.g ., Belize, Heyman et al ., 2001; Mexico, Motta et al ., 2010; Qatar, Robinson et al ., 2013). With a few exceptions ( e.g ., the Galapagos, Hearn et al ., 2016; Tubbataha Reefs Natural Park, TRNP, Philippines, Araujo et al ., 2018), whale shark aggregations tend to be thus primarily driven by foraging opportunities.…”
Section: Figurementioning
confidence: 99%